A systematic review of the application of modern software engineering techniques to the development of robotic systems - Pons, Claudia (2011)
Robots have become usual collaborators in our daily life. While robotic systems grow to be more and more complex, the need to engineering their software development process grows as well. Traditional approaches that are used in the development process of these software systems are reaching their limits; currently used methodologies and toolsets fall short to address the needs of such complex software development process. Separating robotics knowledge from short-cycled implementation technologies is essential to foster reuse and maintenance. This paper presents a systematic review of the current use of modern software engineering techniques for the development of robotic software systems and their actual automation level. The goal of the survey is to summarize the existing evidence concerning the application of such technologies on the robotic systems field; to identify any gaps in current research in order to suggest areas for further investigation and to provide a background in order to appropriately position new research activities.